2016
DOI: 10.1111/eea.12501
|View full text |Cite
|
Sign up to set email alerts
|

Sources of plant resistance to thrips: a potential core component in cotton IPM

Abstract: Thrips (Thysanoptera: Thripidae) are important pests of seedling cotton and their damage can delay crop maturity and/or reduce yield. Plant resistance to thrips in cotton would reduce the need to treat crops with insecticides for their control. This would support integrated pest management strategies by reducing the risk of selecting insecticide resistance in concomitant pests and of disrupting the natural enemy complex. Traits that reduce thrips abundance in cotton are poorly understood, but dense leaf hairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Herbivore-inducible plant defenses are initiated after perception of the herbivore through damage-associated molecular patterns or herbivore-associated molecular patterns. Many authors have reported that several morphological traits were associated with host plant resistance to thrips, such as leaf hair density, leaf hairiness, leaf hardness, leaf wax, glandular hairs, and trichomes [ 9 , 10 , 11 ]. However, biochemical-based defense is considered more effective, as it directly affects insect growth and development [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herbivore-inducible plant defenses are initiated after perception of the herbivore through damage-associated molecular patterns or herbivore-associated molecular patterns. Many authors have reported that several morphological traits were associated with host plant resistance to thrips, such as leaf hair density, leaf hairiness, leaf hardness, leaf wax, glandular hairs, and trichomes [ 9 , 10 , 11 ]. However, biochemical-based defense is considered more effective, as it directly affects insect growth and development [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants have developed highly effective and dynamic defensive strategies against insect pests, including various morphological and biochemical defences that restrict the insect pests, including constitutive defence and induced defence [6,7]. Many authors have reported that several morphological traits were associated with host plant resistance to thrips such as leaf hair density, leaf hairiness, leaf hardness, leaf wax, glandular hairs, and trichomes [8][9][10][11]. However, biochemical-based defence is considered more effective as it directly affects insect growth and development [12].…”
Section: Introductionmentioning
confidence: 99%
“…Skovst resulted in reduced western flower thrips infestation compared with other commonly grown Gossypium hirsutum L. cv. Sicot 71 ( Miyazaki et al, 2017 ). Another study found that thrips infestation was less in glandless cotton than in glandular cotton ( Zhang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%